Communications strategies: An empirical study - Lorna A. Hill; A. A. Archer (South African Journal of Business Management, 1988)
This study, based on the theoretical discussion in the previous article in the series, empirically investigates the communication function in some South African business enterprises. Results indicate that the importance of this function is expected to increase considerably in South African companies in the future. Although an awareness exists of the vital importance of communication, businesses largely seem to neglect using it as a strategic or opinion-forming tool. The emphasis rather appears to be on the tactical use of communication. Furthermore, it is those communication activities directly related to the promotion of the sale of products or services which receive most attention rather than the non-commercial areas of business communication. Employees and customers have the greatest influence on the achievement of long- and short-term corporate goals. However, communication with these two stakeholder groups is the most seriously hampered by cultural, language and literacy obstacles. An analysis of stakeholders in terms of cultural factors forms the foundation for the cultivation of cultural sensitivity which is essential to a proper understanding of the nature of culture and its influence on business communication. Surprisingly, although an awareness exists of the magnitude of cultural differences as a communication obstacle, cultural factors do not receive as much attention as other aspects such as social values, goals and strategies and information required by stakeholders when the stakeholder environment is analysed.Hierdie artikel, gebaseer op die teoretiese bespreking in die vorige artikel in die reeks, ondersoek die kommunikasiefunksie in 'n geselekteerde groep Suid-Afrikaanse sakeondernemings. Resultate dui aan dat hierdie funksie na verwagting in die toekoms in belangrikheid sal toeneem. Alhoewel daar 'n bewustheid bestaan oor die belangrikheid van kommunikasie, skyn dit asof sakeondernemings grootliks versuim om dit as 'n strategiese of meningvormende hulpmiddel te gebruik. Die klem blyk te wees op die taktiese gebruik van kommunikasie. Bowendien word meer aandag aan kommunikasie-aktiwiteite wat te make het met die bevordering van die verkoop van produkte en dienste gegee, eerder as aan die nie-kommersiele areas van sakekommunikasie. Werknemers en klante het die grootste invloed op die bereiking van lang- en korttermyn doelwitte. Kommunikasie met hierdie twee belangegroepe (deelhebbers) word egter ernstig belemmer deur kulturele, taal- en geletterdheidshindernisse. Die ontleding van belangegroepe in terme van kulturele faktore vorm die grondslag van die ontwikkeling van kulturele sensitiwiteit wat noodsaaklik is vir 'n behoorlike begrip van die aard van kultuur en die invloed daarvan op sakekommunkasie. Alhoewel daar 'n bewustheid bestaan van die omvang van kultuurverskille as kommunikasiehindernis, geniet hierdie faktor relatief minder aandag as verskeie ander faktore. In die ontleding van belangegroepe word meer aandag aan aspekte soos die sosiale waardes van belangegroepe, hul doelwitte en strategiee geskenk, asook aan inligting deur hulle benodig.
Keywords: 650